2021
DOI: 10.3389/fnhum.2021.726604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slow Oscillatory Transcranial Alternating Current Stimulation on Motor Cortical Excitability Assessed by Transcranial Magnetic Stimulation

Abstract: Graphical AbstractThirty healthy participants received 60 trials of intermittent SO (0.75 Hz) tACS (1 trial = 16 s on + 16 s off) at an intensity of 2 mA. Motor cortical excitability was assessed using TMS-induced MEPs (blue waveforms) acquired across different oscillatory phases during (i.e., online; red arrows) and outlasting (i.e., offline; green arrows) tACS, as well as at the start and end of the stimulation session (blue arrows). Mean MEP amplitude increased by ∼41% from pre- to post-tACS (P = 0.013); ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
(118 reference statements)
2
6
1
Order By: Relevance
“…It is of interest to note that these facilitatory effects are of a similar magnitude to the facilitatory effects observed in our most recent slow oscillatory tACS study (45.05% increase; Geffen et al, 2021) despite the differences in stimulation frequency, suggesting that these plastic aftereffects may not necessarily be frequency-dependent. When compared to β-tACS (15-25 Hz), which has been previously shown to facilitate resting CSE across multiple studies (Cancelli et al, 2015a;Cancelli et al, 2015b;Feurra et al, 2011;Feurra et al, 2013;Feurra et al, 2019;Heise et al, 2016), a recent meta-analysis by Wischnewski et al (2019) reported that MEP amplitudes were only increased by β-tACS when using electrode montages with a more posterior location for the return electrode (e.g., M1-Pz or M1-Oz) but not when using a conventional M1-supraorbital region montage such as was used in the present study.…”
Section: Aftereffects Of µ-Tacs On Csesupporting
confidence: 77%
See 4 more Smart Citations
“…It is of interest to note that these facilitatory effects are of a similar magnitude to the facilitatory effects observed in our most recent slow oscillatory tACS study (45.05% increase; Geffen et al, 2021) despite the differences in stimulation frequency, suggesting that these plastic aftereffects may not necessarily be frequency-dependent. When compared to β-tACS (15-25 Hz), which has been previously shown to facilitate resting CSE across multiple studies (Cancelli et al, 2015a;Cancelli et al, 2015b;Feurra et al, 2011;Feurra et al, 2013;Feurra et al, 2019;Heise et al, 2016), a recent meta-analysis by Wischnewski et al (2019) reported that MEP amplitudes were only increased by β-tACS when using electrode montages with a more posterior location for the return electrode (e.g., M1-Pz or M1-Oz) but not when using a conventional M1-supraorbital region montage such as was used in the present study.…”
Section: Aftereffects Of µ-Tacs On Csesupporting
confidence: 77%
“…Although we did not observe entrainment of endogenous slow (0.75 Hz) oscillations in our previous experiment (Geffen et al, 2021), we attributed this null result to a lack of resonance dynamics between the eigenfrequency and stimulation frequency (Ali et al, 2013) as well as the relatively small MEP sample size per participant compared to simulation studies (Zoefel et al, 2019). The current study aimed to address both these limitations by using a tailored stimulation frequency that matches the eigenfrequency of the participants' sensorimotor cortex during wake, and by performing multiple experiment sessions for each participant then pooling the data across sessions.…”
Section: Introductioncontrasting
confidence: 69%
See 3 more Smart Citations